PENENTUAN LD50 DAUN CINCO (Cyclea barbata Miers.) PADA MENCIT - Angelina, Marissa; Hartati, Sri; Dewijanti, Indah D; Banjarnahor, Sofna D.S.; Meilawati, Lia (UI Scholars Hub, 2018)
LD50 of Cinco (Cyclea barbata Miers.) Leaf on Mice. The acute toxicity of ethanol extract of Cyclea barbata Miers. (Cb) leaves has been carried out on mice. The extract was administered by oral route in 4 different doses, i.e. 300 mg/kg BW, 1500 mg/kg BW, 3000 mg/kg BW, 30000 mg/kg BW. The toxic effect of the extract were evaluated by observation of behaviour, spinal reflexes, central nervous system, urination, and defecation, and also number of dead animal. The observation period lasted for 14 days. The results showed that up to 30000 mg/kg BW, the test material did not cause any significant toxic effects. The LD50 of the cyclea barbata Miers. leaves on mice was found to be more than 30000 mg/kg BW